The influence of growth temperature on the properties of zinc oxide by thermal oxidation - Nuraini, Abdullah; Noor Mazni, Ismail; Dewan Muhammad, Nuruzzaman (The Malaysian Analytical Sciences Society, 2018)
Zinc thin films were successfully deposited on Si substrate by thermal evaporation method under constant base pressure of 1.604x10-4 Pa. Thermal oxidation of the deposited film was carried out at two different growth temperatures of 300oC and 500oC. The effects of growth temperature on the properties of zinc oxide were investigated. Thermal oxidation for constant time 1 hour in horizontal tube furnace in air condition was carried out. The white-silver zinc thin films were changed to black-brown zinc oxide after thermal oxidation at temperature 500oC. FESEM results show that the zinc particles were almost round shape with nanostructures in size. ZnO nanowires were successfully obtained at low growth temperature of 300oC and the size become decrease as the growth temperature was increased to 500oC. The XRD results confirmed that ZnO was started to oxidize at growth temperature of 300oC with the sharpest peak obtained was indexed to ZnO(101). However, the oxidation of Zn was not fully completed while there are Zn peaks appear at this temperature. At growth temperature 500oC, all the peaks were indexed to ZnO with the sharpest peak was ZnO(101) meaning that the oxidation was completed. The calculated particle sizes were varied from 27.841nm to 36.788nm for ZnO at 300°C and 0.697nm to 161.18nm for ZnO of 500°C.